2016
DOI: 10.1515/amm-2016-0258
|View full text |Cite
|
Sign up to set email alerts
|

Influence of Solution Heat Treatment on Structure and Mechanical Properties of ZnAl22Cu3 Alloy

Abstract: The influence of solution heat treatment at 385°C over 10 h with cooling in water on the structure, hardness and strength of the ZnAl22Cu3 eutectoid alloy is presented in the paper. The eutectoid ZnAl22Cu3 alloy is characterized by a dendritic structure. Dendrites are composed of a supersaturated solid solution of Al in Zn. In the interdendritic spaces a eutectoid mixture is present, with an absence of the ε (CuZn4) phase. Solution heat treatment of the ZnAl22Cu3 alloy causes the occurrence of precipitates ric… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 17 publications
0
2
0
Order By: Relevance
“…Further studies have shown that it has superior mechanical and tribological properties compared to other Zn-Al based alloys and traditional bearing materials (Hekimoglu and Savaskan, 2018;Prasad, 2000;Savaskan and Azaklı, 2008). It was also shown that the mechanical and tribological properties of this alloy can be further improved by application of some heat treatments including T6 and isothermal transformation (Michalik, 2018;Savaşkan and Hekimoğlu, 2015;Savaşkan et al, 2021;Savaşkan et al, in press). The microstructure, mechanical and tribological properties of this alloy have been studied and discussed in detail (Savaşkan et al, 2021;Savaşkan et al, 2022;Savaşkan et al, in press), but no study has been conducted on the correlation of its mechanical and tribological properties.…”
Section: Introductionmentioning
confidence: 93%
“…Further studies have shown that it has superior mechanical and tribological properties compared to other Zn-Al based alloys and traditional bearing materials (Hekimoglu and Savaskan, 2018;Prasad, 2000;Savaskan and Azaklı, 2008). It was also shown that the mechanical and tribological properties of this alloy can be further improved by application of some heat treatments including T6 and isothermal transformation (Michalik, 2018;Savaşkan and Hekimoğlu, 2015;Savaşkan et al, 2021;Savaşkan et al, in press). The microstructure, mechanical and tribological properties of this alloy have been studied and discussed in detail (Savaşkan et al, 2021;Savaşkan et al, 2022;Savaşkan et al, in press), but no study has been conducted on the correlation of its mechanical and tribological properties.…”
Section: Introductionmentioning
confidence: 93%
“…These materials exhibit a high specific strength and stiffness, a good resistance to corrosion, cavitation wear in different environments and a competitive price relative to conventional high temperature nickel based superalloys. Furthermore, the performance of Ni 3 Al intermetallic alloys can be formed in a wide range by a proper selection of alloying elements, the conditions of crystallization and processing technology [8][9][10]. The Ni 3 Al -based intermetallic alloys have already found or it is expected that will find in the next few years some application in the steel, automotive or chemical industry [11][12].…”
Section: Introductionmentioning
confidence: 99%